(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Janatiningrum I, Lestari Y. 2022. Enzyme production, antibacterial and antifungal activities of actinobacteria isolated from Ficus deltoidea rhizosphere. Biodiversitas 23: 1950-1957. Actinobacteria have long been known to have the ability to produce bioactive compounds and secondary metabolites. Actinobacteria from the rhizosphere of Ficus deltoidea Jack were expected to produce beneficial secondary metabolite compounds with antibacterial, antifungal activity, and enzymes. A total of 34 different actinobacteria were isolated from F. deltoidea rhizosphere soil. They were assessed for their antimicrobial activity against four fungi, four bacteria, and enzymatic activity. The enzyme activity test showed that almost all isolates had amylase, protease, and cellulase activities. The results of antibacterial indicated that 61.8% of all isolates are active against bacterial tested, i.e., Bacillus subtilis ATTC 3061 (10), Staphylococcus aureus ATCC 6538 (13), and Escherichia coli ATCC 8739 (3). The antifungal test showed that 64.8% of the isolates had antifungal activity against four fungal tested, i.e., Fusarium oxysporum (13), Candida albicans (7), Colletotrichum capsici (17). Based on the enzymes production, antibacterial activity, and antifungal activity, RTB 1 and RTB 34 isolates were selected to be characterized by morphological and 16S rRNA gene identification. The morphological characterization and molecular identification showed that RTB 1 and RTB 34 belong to the Streptomyces genus. This study indicated that the selected actinomycetes could be antimicrobial and enzyme sources.